Epidermal parasitic skin diseases: a neglected category of poverty-associated plagues - Hermann Feldmeier; Jorg Heukelbach (The World Health Organization, 2009)
Epidermal parasitic skin diseases (EPSD) are a heterogeneous category of infectious diseases in which parasite-host interactions are confined to the upper layer of the skin. The six major EPSD are scabies, pediculosis (capitis, corporis and pubis), tungiasis and hookworm-related cutaneous larva migrans. We summarize the current knowledge on EPSD and show that these diseases are widespread, polyparasitism is common, and significant primary and secondary morbidity occurs. We show that poverty favours the presence of animal reservoirs, ensures ongoing transmission, facilitates atypical methods of spreading infectious agents and increases the chances of exposure. This results in an extraordinarily high prevalence and intensity of infestation of EPSD in resource-poor populations. Stigma, lack of access to health care and deficient behaviour in seeking health care are the reasons why EPSD frequently progress untreated and why in resource-poor populations severe morbidity is common. The ongoing uncontrolled urbanization in many developing countries makes it likely that EPSD will remain the overriding parasitic diseases for people living in extreme poverty. We advocate integrating control of EPSD into intervention measures directed against other neglected diseases such as filariasis and intestinal helminthiases.